Implementation of Circular Economy Business Model in Inorganic Waste Management Mechanism in Tegal Tugu Village, Gianyar, Bali - Ni Wayan Nadeya Komala MAHARANI; Ni Putu Amanda Salsabila Ariyasa PUTRI; Natasya Agnes Rakhel SIHOMBING; Ni Putu Deswitha Lestari DEWI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:This study analyzes the application of a circular economy business model in the management of inorganic waste in Tegal Tugu Village, Gianyar, with the problem of high volumes of inorganic waste, if not managed properly, can cause environmental pollution, reduce the quality of life of the community, and increase the risk of long-term environmental damage.Methodology:Circular economy businesses use an innovative approach to waste management by prioritizing the principles of reduce, reuse, and recycle (3R), which aim to minimize the impact of waste on the environment.Findings:This study examines various strategies that can be applied to optimize inorganic waste management, including recycling, reusing, and reducing waste generation. Through case studies and policy analysis, the implementation of efficient reuse, recycling, and processing strategies not only reduces environmental impacts but also provides economic opportunities through job creation and product innovation.Implication:Data analysis is carried out thematically to identify the relationship between inorganic waste management, environmental sustainability, and the potential economic value generated. The results of this method will be presented in the form of an in-depth analysis of the challenges and opportunities for implementing a sustainability model in Tegal Tugu Village.